Maḍiyānī śreṣṭha vārtāo - Maḍiyā, Cunīlāla (Navabhārata Sāhitya Mandira, 2010)
Selected short stories of a Gujarati author
Short stories. - In Gujarati-Schr
Keywords: Gujarātī-Sprache; Kurzgeschichte; Geschichte 1900-2000